(untitled) (Research, Society and Development, 2022)
The phylum Basidiomycota represents one of the most diverse groups of fungi. In this phylum the order Agaricales has great ecological and economic value. However, this order is little studied in Brazil. Thus, in an attempt to contribute to the scientific knowledge about this taxon, in this study we evaluated trends and gaps in scientific production on Agaricales. We searched for studies on Agaricales in Brazil, published in the period from 1980 to 2020, by using the Web of Science and Scopus databases, using the following word and Booleans indexers combinations: Agaricales OR Agaric* AND Brazil*. We found a total of 824 documents on Agaricales in Brazil in the studied period, with an increase in the number of studies associated with the time scale. In the Southeast, Northeast and South regions of the country are the largest centers of scientific production on Agaricales, with emphasis on the Federal Universities of Minas Gerais, Pernambuco and Paraná, which have greater structures and trained human resources compared to other research centers. Brazilians. Wartchow F, Gibertoni T and Capelari M were the outstanding authors of publications on this topic. The trend in the studies was evidenced by greater use of the following keywords: Agaricales, basidiomycota, Brazil, fungi and mushroom. Gaps in knowledge are found in Brazilian regions where studies in the mycological field are still incipient. The data demonstrate the need to expand the studies of the Brazilian Funga, which will contribute to the expansion of knowledge on richness, diversity and economic potential of species.